Thermally Conductive General-Purpose Polystyrene (GPPS)/Graphite Composite with a Segregated Structure: Effect of Size of Resin and Graphite Flakes. Issue 13 (2nd September 2018) - Gao, Chuanwei; Feng, Changping; Lu, Hui; Ni, Haiying; Chen, Jun
ABSTRACT: General-purpose polystyrene (GPPS)/graphite flake composites with a segregated structure were fabricated by newly developed binder mixing method, aiming at highly thermally conductive polymer composites. The coefficient of thermal conductivity of the GPPS/graphite composites can be easily improved to be 3.5 W m −1  k −1 at a graphite flakes loading of 24.7 vol%, showing an improvement of more than 2, 000% compared with pure GPPS. The thermal conductivity of the composites increased with the increasing particle size of graphite flakes, while the mechanical properties of composites are decreased with the increasing particle size of GPPS resin particles. GRAPHICAL ABSTRACT: